Ecotoxicological Assessment of Immersion Samples from Facade Render Containing Free or Encapsulated Biocides. (11th July 2018) - Vermeirssen, Etiënne L. M.; Campiche, Sophie; Dietschweiler, Conrad; Werner, Inge; Burkhardt, Michael
Abstract: To protect house facades from fouling by microorganisms, biocides can be added to a render or paint before it is applied. During driving rain events, these biocides gradually leach out and have the potential to pollute soil or aquatic ecosystems. We studied the leaching behavior of biocides and toxicity of leachates from renders with either free or encapsulated biocides. Both render types contained equal amounts of terbutryn, 2‐octyl‐3(2H)‐isothiazolinone (OIT), and 4, 5‐dichloro‐2‐n‐octyl‐4‐isothiazolino‐3‐one (DCOIT). Nine leachate samples were generated over 9 immersion cycles according to a European standard, and biocides were quantified. The first and ninth leachate samples were tested using bioassays with algae, bacteria, and water fleas, the first sample was also tested with earthworms and springtails. Encapsulation reduced leaching of terbutryn, OIT, and DCOIT by 4‐, 17‐, and 27‐fold. For aquatic organisms, the toxicity of water from render containing encapsulated biocides was always lower than that of render with free biocides. Furthermore, toxicity decreased by 4‐ to 5‐fold over the 9 immersion cycles. Inhibition of photosynthesis was the most sensitive endpoint, followed by algal growth rate, bacterial bioluminescence, and water flea reproduction. Toxicity to algae was due to terbutryn and toxicity to bacteria was due to OIT. None of the samples affected soil organisms. Results demonstrate that combining standardized leaching tests with standardized bioassays is a promising approach to evaluate the ecotoxicity of biocides that leach from facade renders. Environ Toxicol Chem 2018;37:2246–2256. © 2018 SETAC Abstract : Facade render with biocides was applied to extruded polystyrene panels and immersed in water. Leachate samples were analyzed in various aquatic and terrestrial bioassays for toxic effects.